Active films based on alginate containing lemongrass essential oil encapsulated: Effect of process and storage conditions - Riquelme, Natalia (2017)
Antimicrobial active films are studied to increase fresh food shelf life. The aim of this study was to evaluate the effect of process and storage conditions on physical properties and antimicrobial activity of alginate-based films with encapsulated lemongrass essential oil. Films were obtained from film forming emulsions with different droplet sizes (2.9 ± 0.2 μm and 0.43 ± 0.02 μm), containing 1%w/w alginate, 1%w/w sorbitol, 0.75%w/w?1.35%w/w sodium caseinate, 0.5%w/v lemongrass essential oil and 0.02%w/w calcium carbonate. Each film was characterized by physical properties and antimicrobial activity against Escherichia coli and Botrytis cinerea. Films were evaluated in different storage conditions (75%RH, 4 °C; 75%RH, 20 °C; 11%RH, 4 °C; 11%RH, 20 °C). Droplet sizes of film forming emulsions affected significantly the physical properties and antimicrobial activity of films, being more effective large droplet size. Particularly, high concentration of sodium caseinate affected optical properties of films. Moreover, storage conditions affected antimicrobial activity of films. The greatest inhibition of microbial growth was observed at 4 °C, reaching the highest percentages, after 15 days of storage, demonstrating the release of the active agent in a prolonged manner. In conclusion, differences in sustained release of the antimicrobial depended mainly on the processing and storage conditions of active film.